Management of Linezolid-Induced Anemia in Drug-Resistant Tuberculosis Therapy: A Literature Review - Ayu Sekarani Damana Putri (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Linezolid is a Class A drug recommended for the treatment of multidrug-resistant tuberculosis (TB), but its use carries a significant risk of hematologic toxicity, particularly anemia. The optimal duration and dose for linezolid therapy are still not fully known. Objective: This systematic review aimed to evaluate strategies to manage anemia in patients with drug-resistant TB receiving linezolid therapy. Methods: Articles were searched through Science Direct, PubMed, and Google Scholar databases for articles published between 2014 and 2024. The keywords used were “tuberculosis resistant drugs”, “linezolid”, “hematology toxicity”, and “anemia”. Results: From the literature review, linezolid can cause anemia through the mechanism of inhibition of mitochondrial protein synthesis in erythropoiesis progenitor cells in the bone marrow and suppression of hematopoiesis. Major risk factors include long-term use (>8 weeks), high doses (>600 mg/day), and comorbid conditions such as malnutrition and liver disease. Management includes close monitoring of hemoglobin, dose reduction, discontinuation of therapy when necessary, and administration of hematopoietic supplements. Conclusion: Linezolid-induced anemia can significantly affect the continuation of therapy and quality of life of patients. The management strategies that can be applied depend on the severity of the anemia. Close monitoring and early intervention are essential to ensure successful treatment.